lean2/library/data/int/basic.lean

795 lines
33 KiB
Text
Raw Normal View History

/-
Copyright (c) 2014 Floris van Doorn. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Module: int.basic
Authors: Floris van Doorn, Jeremy Avigad
The integers, with addition, multiplication, and subtraction. The representation of the integers is
chosen to compute efficiently; see the examples in the comments at the end of this file.
To faciliate proving things about these operations, we show that the integers are a quotient of
× with the usual equivalence relation ≡, and functions
abstr : ×
repr : ×
satisfying
abstr_repr (a : ) : abstr (repr a) = a
repr_abstr (p : × ) : repr (abstr p) ≡ p
abstr_eq (p q : × ) : p ≡ q → abstr p = abstr q
For example, to "lift" statements about add to statements about padd, we need to prove the
following:
repr_add (a b : ) : repr (a + b) = padd (repr a) (repr b)
padd_congr (p p' q q' : × ) (H1 : p ≡ p') (H2 : q ≡ q') : padd p q ≡ p' q'
-/
import data.nat.basic data.nat.order data.nat.sub data.prod
import algebra.relation algebra.binary algebra.ordered_ring
import tools.fake_simplifier
open eq.ops
open prod relation nat
open decidable binary fake_simplifier
/- the type of integers -/
inductive int : Type :=
of_nat : nat → int,
neg_succ_of_nat : nat → int
notation `` := int
coercion [persistent] int.of_nat
definition int.of_num [coercion] (n : num) : := int.of_nat (nat.of_num n)
namespace int
/- definitions of basic functions -/
definition neg_of_nat (m : ) : :=
nat.cases_on m 0 (take m', neg_succ_of_nat m')
definition sub_nat_nat (m n : ) : :=
nat.cases_on (n - m)
(of_nat (m - n)) -- m ≥ n
(take k, neg_succ_of_nat k) -- m < n, and n - m = succ k
definition neg (a : ) : :=
cases_on a
(take m, -- a = of_nat m
nat.cases_on m 0 (take m', neg_succ_of_nat m'))
(take m, of_nat (succ m)) -- a = neg_succ_of_nat m
definition add (a b : ) : :=
cases_on a
(take m, -- a = of_nat m
cases_on b
(take n, of_nat (m + n)) -- b = of_nat n
(take n, sub_nat_nat m (succ n))) -- b = neg_succ_of_nat n
(take m, -- a = neg_succ_of_nat m
cases_on b
(take n, sub_nat_nat n (succ m)) -- b = of_nat n
(take n, neg_of_nat (succ m + succ n))) -- b = neg_succ_of_nat n
definition mul (a b : ) : :=
cases_on a
(take m, -- a = of_nat m
cases_on b
(take n, of_nat (m * n)) -- b = of_nat n
(take n, neg_of_nat (m * succ n))) -- b = neg_succ_of_nat n
(take m, -- a = neg_succ_of_nat m
cases_on b
(take n, neg_of_nat (succ m * n)) -- b = of_nat n
(take n, of_nat (succ m * succ n))) -- b = neg_succ_of_nat n
/- notation -/
notation `-[` n `+1]` := int.neg_succ_of_nat n -- for pretty-printing output
prefix - := int.neg
infix + := int.add
infix * := int.mul
/- some basic functions and properties -/
theorem of_nat_inj {m n : } (H : of_nat m = of_nat n) : m = n :=
no_confusion H (λe, e)
theorem neg_succ_of_nat_inj {m n : } (H : neg_succ_of_nat m = neg_succ_of_nat n) : m = n :=
no_confusion H (λe, e)
definition has_decidable_eq [instance] : decidable_eq :=
take a b,
cases_on a
(take m,
cases_on b
(take n,
if H : m = n then inl (congr_arg of_nat H) else inr (take H1, H (of_nat_inj H1)))
(take n', inr (assume H, no_confusion H)))
(take m',
cases_on b
(take n, inr (assume H, no_confusion H))
(take n',
(if H : m' = n' then inl (congr_arg neg_succ_of_nat H) else
inr (take H1, H (neg_succ_of_nat_inj H1)))))
theorem add_of_nat (n m : nat) : of_nat n + of_nat m = #nat n + m := rfl
theorem of_nat_succ (n : ) : of_nat (succ n) = of_nat n + 1 := rfl
theorem mul_of_nat (n m : ) : of_nat n * of_nat m = n * m := rfl
theorem sub_nat_nat_of_ge {m n : } (H : m ≥ n) : sub_nat_nat m n = of_nat (m - n) :=
have H1 : n - m = 0, from le_imp_sub_eq_zero H,
calc
sub_nat_nat m n = nat.cases_on 0 (of_nat (m - n)) _ : H1 ▸ rfl
... = of_nat (m - n) : rfl
theorem sub_nat_nat_of_lt {m n : } (H : m < n) :
sub_nat_nat m n = neg_succ_of_nat (pred (n - m)) :=
have H1 : n - m = succ (pred (n - m)), from (succ_pred_of_pos (sub_pos_of_gt H))⁻¹,
calc
sub_nat_nat m n = nat.cases_on (succ (pred (n - m))) (of_nat (m - n))
(take k, neg_succ_of_nat k) : H1 ▸ rfl
... = neg_succ_of_nat (pred (n - m)) : rfl
definition nat_abs (a : ) : := cases_on a (take n, n) (take n', succ n')
theorem nat_abs_of_nat (n : ) : nat_abs (of_nat n) = n := rfl
theorem nat_abs_eq_zero {a : } : nat_abs a = 0 → a = 0 :=
cases_on a
(take m, assume H : nat_abs (of_nat m) = 0, congr_arg of_nat H)
(take m', assume H : nat_abs (neg_succ_of_nat m') = 0, absurd H (succ_ne_zero _))
/-
Show int is a quotient of ordered pairs of natural numbers, with the usual
equivalence relation.
-/
definition equiv (p q : × ) : Prop := pr1 p + pr2 q = pr2 p + pr1 q
notation [local] p `≡` q := equiv p q
theorem equiv.refl {p : × } : p ≡ p := !add.comm
theorem equiv.symm {p q : × } (H : p ≡ q) : q ≡ p :=
calc
pr1 q + pr2 p = pr2 p + pr1 q : !add.comm
... = pr1 p + pr2 q : H⁻¹
... = pr2 q + pr1 p : !add.comm
theorem equiv.trans {p q r : × } (H1 : p ≡ q) (H2 : q ≡ r) : p ≡ r :=
have H3 : pr1 p + pr2 r + pr2 q = pr2 p + pr1 r + pr2 q, from
calc
pr1 p + pr2 r + pr2 q = pr1 p + pr2 q + pr2 r : by simp
... = pr2 p + pr1 q + pr2 r : {H1}
... = pr2 p + (pr1 q + pr2 r) : by simp
... = pr2 p + (pr2 q + pr1 r) : {H2}
... = pr2 p + pr1 r + pr2 q : by simp,
show pr1 p + pr2 r = pr2 p + pr1 r, from add.cancel_right H3
theorem equiv_equiv : is_equivalence equiv :=
is_equivalence.mk @equiv.refl @equiv.symm @equiv.trans
theorem equiv_cases {p q : × } (H : equiv p q) :
(pr1 p ≥ pr2 p ∧ pr1 q ≥ pr2 q) (pr1 p < pr2 p ∧ pr1 q < pr2 q) :=
or.elim (@le_or_gt (pr2 p) (pr1 p))
(assume H1: pr1 p ≥ pr2 p,
have H2 : pr2 p + pr1 q ≥ pr2 p + pr2 q, from H ▸ add_le_right H1 (pr2 q),
or.inl (and.intro H1 (add_le_cancel_left H2)))
(assume H1: pr1 p < pr2 p,
have H2 : pr2 p + pr1 q < pr2 p + pr2 q, from H ▸ add_lt_right H1 (pr2 q),
or.inr (and.intro H1 (add_lt_cancel_left H2)))
theorem equiv_of_eq {p q : × } (H : p = q) : p ≡ q := H ▸ equiv.refl
theorem equiv_of_eq_of_equiv {p q r : × } (H1 : p = q) (H2 : q ≡ r) : p ≡ r := H1⁻¹ ▸ H2
theorem equiv_of_equiv_of_eq {p q r : × } (H1 : p ≡ q) (H2 : q = r) : p ≡ r := H2 ▸ H1
calc_trans equiv.trans
calc_refl equiv.refl
calc_symm equiv.symm
calc_trans equiv_of_eq_of_equiv
calc_trans equiv_of_equiv_of_eq
/- the representation and abstraction functions -/
definition abstr (a : × ) : := sub_nat_nat (pr1 a) (pr2 a)
theorem abstr_of_ge {p : × } (H : pr1 p ≥ pr2 p) : abstr p = of_nat (pr1 p - pr2 p) :=
sub_nat_nat_of_ge H
theorem abstr_of_lt {p : × } (H : pr1 p < pr2 p) :
abstr p = neg_succ_of_nat (pred (pr2 p - pr1 p)) :=
sub_nat_nat_of_lt H
definition repr (a : ) : × := cases_on a (take m, (m, 0)) (take m, (0, succ m))
theorem abstr_repr (a : ) : abstr (repr a) = a :=
cases_on a (take m, (sub_nat_nat_of_ge (zero_le m))) (take m, rfl)
theorem repr_sub_nat_nat (m n : ) : repr (sub_nat_nat m n) ≡ (m, n) :=
or.elim (@le_or_gt n m)
(take H : m ≥ n,
have H1 : repr (sub_nat_nat m n) = (m - n, 0), from sub_nat_nat_of_ge H ▸ rfl,
H1⁻¹ ▸
(calc
m - n + n = m : add_sub_ge_left H
... = 0 + m : add.zero_left))
(take H : m < n,
have H1 : repr (sub_nat_nat m n) = (0, succ (pred (n - m))), from sub_nat_nat_of_lt H ▸ rfl,
H1⁻¹ ▸
(calc
0 + n = n : add.zero_left
... = n - m + m : add_sub_ge_left (lt_imp_le H)
... = succ (pred (n - m)) + m : (succ_pred_of_pos (sub_pos_of_gt H))⁻¹))
theorem repr_abstr (p : × ) : repr (abstr p) ≡ p :=
!prod.eta ▸ !repr_sub_nat_nat
theorem abstr_eq {p q : × } (Hequiv : p ≡ q) : abstr p = abstr q :=
or.elim (equiv_cases Hequiv)
(assume H2,
have H3 : pr1 p ≥ pr2 p, from and.elim_left H2,
have H4 : pr1 q ≥ pr2 q, from and.elim_right H2,
have H5 : pr1 p = pr1 q - pr2 q + pr2 p, from
calc
pr1 p = pr1 p + pr2 q - pr2 q : sub_add_left
... = pr2 p + pr1 q - pr2 q : Hequiv
... = pr2 p + (pr1 q - pr2 q) : add_sub_assoc H4
... = pr1 q - pr2 q + pr2 p : add.comm,
have H6 : pr1 p - pr2 p = pr1 q - pr2 q, from
calc
pr1 p - pr2 p = pr1 q - pr2 q + pr2 p - pr2 p : H5
... = pr1 q - pr2 q : sub_add_left,
abstr_of_ge H3 ⬝ congr_arg of_nat H6 ⬝ (abstr_of_ge H4)⁻¹)
(assume H2,
have H3 : pr1 p < pr2 p, from and.elim_left H2,
have H4 : pr1 q < pr2 q, from and.elim_right H2,
have H5 : pr2 p = pr2 q - pr1 q + pr1 p, from
calc
pr2 p = pr2 p + pr1 q - pr1 q : sub_add_left
... = pr1 p + pr2 q - pr1 q : Hequiv
... = pr1 p + (pr2 q - pr1 q) : add_sub_assoc (lt_imp_le H4)
... = pr2 q - pr1 q + pr1 p : add.comm,
have H6 : pr2 p - pr1 p = pr2 q - pr1 q, from
calc
pr2 p - pr1 p = pr2 q - pr1 q + pr1 p - pr1 p : H5
... = pr2 q - pr1 q : sub_add_left,
abstr_of_lt H3 ⬝ congr_arg neg_succ_of_nat (congr_arg pred H6)⬝ (abstr_of_lt H4)⁻¹)
theorem equiv_iff (p q : × ) : (p ≡ q) ↔ ((p ≡ p) ∧ (q ≡ q) ∧ (abstr p = abstr q)) :=
iff.intro
(assume H : equiv p q,
and.intro !equiv.refl (and.intro !equiv.refl (abstr_eq H)))
(assume H : equiv p p ∧ equiv q q ∧ abstr p = abstr q,
have H1 : abstr p = abstr q, from and.elim_right (and.elim_right H),
equiv.trans (H1 ▸ equiv.symm (repr_abstr p)) (repr_abstr q))
theorem eq_abstr_of_equiv_repr {a : } {p : × } (Hequiv : repr a ≡ p) : a = abstr p :=
calc
a = abstr (repr a) : abstr_repr
... = abstr p : abstr_eq Hequiv
theorem eq_of_repr_equiv_repr {a b : } (H : repr a ≡ repr b) : a = b :=
calc
a = abstr (repr a) : abstr_repr
... = abstr (repr b) : abstr_eq H
... = b : abstr_repr
theorem nat_abs_abstr (p : × ) : nat_abs (abstr p) = dist (pr1 p) (pr2 p) :=
let m := pr1 p, n := pr2 p in
or.elim (@le_or_gt n m)
(assume H : m ≥ n,
calc
nat_abs (abstr (m, n)) = nat_abs (of_nat (m - n)) : int.abstr_of_ge H
... = dist m n : dist_ge H)
(assume H : m < n,
calc
nat_abs (abstr (m, n)) = nat_abs (neg_succ_of_nat (pred (n - m))) : int.abstr_of_lt H
... = succ (pred (n - m)) : rfl
... = n - m : succ_pred_of_pos (sub_pos_of_gt H)
... = dist m n : dist_le (lt_imp_le H))
theorem cases_of_nat (a : ) : (∃n : , a = of_nat n) (∃n : , a = - of_nat n) :=
cases_on a
(take n, or.inl (exists.intro n rfl))
(take n', or.inr (exists.intro (succ n') rfl))
theorem cases_of_nat_succ (a : ) : (∃n : , a = of_nat n) (∃n : , a = - (of_nat (succ n))) :=
int.cases_on a (take m, or.inl (exists.intro _ rfl)) (take m, or.inr (exists.intro _ rfl))
theorem by_cases_of_nat {P : → Prop} (a : )
(H1 : ∀n : , P (of_nat n)) (H2 : ∀n : , P (- of_nat n)) :
P a :=
or.elim (cases_of_nat a)
(assume H, obtain (n : ) (H3 : a = n), from H, H3⁻¹ ▸ H1 n)
(assume H, obtain (n : ) (H3 : a = -n), from H, H3⁻¹ ▸ H2 n)
theorem by_cases_of_nat_succ {P : → Prop} (a : )
(H1 : ∀n : , P (of_nat n)) (H2 : ∀n : , P (- of_nat (succ n))) :
P a :=
or.elim (cases_of_nat_succ a)
(assume H, obtain (n : ) (H3 : a = n), from H, H3⁻¹ ▸ H1 n)
(assume H, obtain (n : ) (H3 : a = -(succ n)), from H, H3⁻¹ ▸ H2 n)
/-
Show int is a ring.
-/
/- addition -/
definition padd (p q : × ) : × := map_pair2 nat.add p q
theorem repr_add (a b : ) : repr (add a b) ≡ padd (repr a) (repr b) :=
cases_on a
(take m,
cases_on b
(take n, !equiv.refl)
(take n',
have H1 : equiv (repr (add (of_nat m) (neg_succ_of_nat n'))) (m, succ n'),
from !repr_sub_nat_nat,
have H2 : padd (repr (of_nat m)) (repr (neg_succ_of_nat n')) = (m, 0 + succ n'),
from rfl,
(!add.zero_left ▸ H2)⁻¹ ▸ H1))
(take m',
cases_on b
(take n,
have H1 : equiv (repr (add (neg_succ_of_nat m') (of_nat n))) (n, succ m'),
from !repr_sub_nat_nat,
have H2 : padd (repr (neg_succ_of_nat m')) (repr (of_nat n)) = (0 + n, succ m'),
from rfl,
(!add.zero_left ▸ H2)⁻¹ ▸ H1)
(take n',!repr_sub_nat_nat))
theorem padd_congr {p p' q q' : × } (Ha : p ≡ p') (Hb : q ≡ q') : padd p q ≡ padd p' q' :=
calc
pr1 (padd p q) + pr2 (padd p' q') = pr1 p + pr2 p' + (pr1 q + pr2 q') : by simp
... = pr2 p + pr1 p' + (pr1 q + pr2 q') : {Ha}
... = pr2 p + pr1 p' + (pr2 q + pr1 q') : {Hb}
... = pr2 (padd p q) + pr1 (padd p' q') : by simp
theorem padd_comm (p q : × ) : padd p q = padd q p :=
calc
padd p q = (pr1 p + pr1 q, pr2 p + pr2 q) : rfl
... = (pr1 q + pr1 p, pr2 p + pr2 q) : add.comm
... = (pr1 q + pr1 p, pr2 q + pr2 p) : add.comm
... = padd q p : rfl
theorem padd_assoc (p q r : × ) : padd (padd p q) r = padd p (padd q r) :=
calc
padd (padd p q) r = (pr1 p + pr1 q + pr1 r, pr2 p + pr2 q + pr2 r) : rfl
... = (pr1 p + (pr1 q + pr1 r), pr2 p + pr2 q + pr2 r) : add.assoc
... = (pr1 p + (pr1 q + pr1 r), pr2 p + (pr2 q + pr2 r)) : add.assoc
... = padd p (padd q r) : rfl
theorem add.comm (a b : ) : a + b = b + a :=
begin
apply eq_of_repr_equiv_repr,
apply equiv.trans,
apply repr_add,
apply equiv.symm,
apply (eq.subst (padd_comm (repr b) (repr a))),
apply repr_add
end
theorem add.assoc (a b c : ) : a + b + c = a + (b + c) :=
have H1 [visible]: repr (a + b + c) ≡ padd (padd (repr a) (repr b)) (repr c), from
equiv.trans (repr_add (a + b) c) (padd_congr !repr_add !equiv.refl),
have H2 [visible]: repr (a + (b + c)) ≡ padd (repr a) (padd (repr b) (repr c)), from
equiv.trans (repr_add a (b + c)) (padd_congr !equiv.refl !repr_add),
begin
apply eq_of_repr_equiv_repr,
apply equiv.trans,
apply H1,
apply (eq.subst ((padd_assoc _ _ _)⁻¹)),
apply equiv.symm,
apply H2
end
theorem add.right_id (a : ) : a + 0 = a := cases_on a (take m, rfl) (take m', rfl)
theorem add.left_id (a : ) : 0 + a = a := add.comm a 0 ▸ add.right_id a
/- negation -/
definition pneg (p : × ) : × := (pr2 p, pr1 p)
-- note: this is =, not just ≡
theorem repr_neg (a : ) : repr (- a) = pneg (repr a) :=
cases_on a
(take m,
nat.cases_on m rfl (take m', rfl))
(take m', rfl)
theorem pneg_congr {p p' : × } (H : p ≡ p') : pneg p ≡ pneg p' := eq.symm H
theorem pneg_pneg (p : × ) : pneg (pneg p) = p := !prod.eta
theorem nat_abs_neg (a : ) : nat_abs (-a) = nat_abs a :=
calc
nat_abs (-a) = nat_abs (abstr (repr (-a))) : abstr_repr
... = nat_abs (abstr (pneg (repr a))) : repr_neg
... = dist (pr1 (pneg (repr a))) (pr2 (pneg (repr a))) : nat_abs_abstr
... = dist (pr2 (pneg (repr a))) (pr1 (pneg (repr a))) : dist_comm
... = nat_abs (abstr (repr a)) : nat_abs_abstr
... = nat_abs a : abstr_repr
theorem padd_pneg (p : × ) : padd p (pneg p) ≡ (0, 0) :=
show pr1 p + pr2 p + 0 = pr2 p + pr1 p + 0, from !nat.add.comm ▸ rfl
theorem padd_padd_pneg (p q : × ) : padd (padd p q) (pneg q) ≡ p :=
show pr1 p + pr1 q + pr2 q + pr2 p = pr2 p + pr2 q + pr1 q + pr1 p, by simp
theorem add.left_inv (a : ) : -a + a = 0 :=
have H : repr (-a + a) ≡ repr 0, from
calc
repr (-a + a) ≡ padd (repr (neg a)) (repr a) : repr_add
... = padd (pneg (repr a)) (repr a) : repr_neg
... ≡ repr 0 : padd_pneg,
eq_of_repr_equiv_repr H
/- nat -/
definition pabs (p : × ) : := dist (pr1 p) (pr2 p)
theorem pabs_congr {p q : × } (H : p ≡ q) : pabs p = pabs q :=
calc
pabs p = nat_abs (abstr p) : nat_abs_abstr
... = nat_abs (abstr q) : abstr_eq H
... = pabs q : nat_abs_abstr
theorem nat_abs_eq_pabs_repr (a : ) : nat_abs a = pabs (repr a) :=
calc
nat_abs a = nat_abs (abstr (repr a)) : abstr_repr
... = pabs (repr a) : nat_abs_abstr
theorem nat_abs_add_le (a b : ) : nat_abs (a + b) ≤ nat_abs a + nat_abs b :=
have H : nat_abs (a + b) = pabs (padd (repr a) (repr b)), from
calc
nat_abs (a + b) = pabs (repr (a + b)) : nat_abs_eq_pabs_repr
... = pabs (padd (repr a) (repr b)) : pabs_congr !repr_add,
have H1 : nat_abs a = pabs (repr a), from !nat_abs_eq_pabs_repr,
have H2 : nat_abs b = pabs (repr b), from !nat_abs_eq_pabs_repr,
have H3 : pabs (padd (repr a) (repr b)) ≤ pabs (repr a) + pabs (repr b), from !dist_add_le_add_dist,
H⁻¹ ▸ H1⁻¹ ▸ H2⁻¹ ▸ H3
theorem mul_nat_abs (a b : ) : nat_abs (a * b) = #nat (nat_abs a) * (nat_abs b) :=
cases_on a
(take m,
cases_on b
(take n, rfl)
(take n', !nat_abs_neg ▸ rfl))
(take m',
cases_on b
(take n, !nat_abs_neg ▸ rfl)
(take n', rfl))
/- multiplication -/
definition pmul (p q : × ) : × :=
(pr1 p * pr1 q + pr2 p * pr2 q, pr1 p * pr2 q + pr2 p * pr1 q)
theorem repr_neg_of_nat (m : ) : repr (neg_of_nat m) = (0, m) :=
nat.cases_on m rfl (take m', rfl)
-- note: we have =, not just ≡
theorem repr_mul (a b : ) : repr (mul a b) = pmul (repr a) (repr b) :=
cases_on a
(take m,
cases_on b
(take n,
(calc
pmul (repr m) (repr n) = (m * n + 0 * 0, m * 0 + 0 * n) : rfl
... = (m * n + 0 * 0, m * 0 + 0) : mul.zero_left)⁻¹)
(take n',
(calc
pmul (repr m) (repr (neg_succ_of_nat n')) =
(m * 0 + 0 * succ n', m * succ n' + 0 * 0) : rfl
... = (m * 0 + 0, m * succ n' + 0 * 0) : mul.zero_left
... = repr (mul m (neg_succ_of_nat n')) : repr_neg_of_nat)⁻¹))
(take m',
cases_on b
(take n,
(calc
pmul (repr (neg_succ_of_nat m')) (repr n) =
(0 * n + succ m' * 0, 0 * 0 + succ m' * n) : rfl
... = (0 + succ m' * 0, 0 * 0 + succ m' * n) : mul.zero_left
... = (0 + succ m' * 0, succ m' * n) : add.zero_left
... = repr (mul (neg_succ_of_nat m') n) : repr_neg_of_nat)⁻¹)
(take n',
(calc
pmul (repr (neg_succ_of_nat m')) (repr (neg_succ_of_nat n')) =
(0 + succ m' * succ n', 0 * succ n') : rfl
... = (succ m' * succ n', 0 * succ n') : add.zero_left
... = (succ m' * succ n', 0) : mul.zero_left
... = repr (mul (neg_succ_of_nat m') (neg_succ_of_nat n')) : rfl)⁻¹))
theorem equiv_mul_prep {xa ya xb yb xn yn xm ym : }
(H1 : xa + yb = ya + xb) (H2 : xn + ym = yn + xm)
: xa * xn + ya * yn + (xb * ym + yb * xm) = xa * yn + ya * xn + (xb * xm + yb * ym) :=
have H3 : xa * xn + ya * yn + (xb * ym + yb * xm) + (yb * xn + xb * yn + (xb * xn + yb * yn))
= xa * yn + ya * xn + (xb * xm + yb * ym) + (yb * xn + xb * yn + (xb * xn + yb * yn)), from
calc
xa * xn + ya * yn + (xb * ym + yb * xm) + (yb * xn + xb * yn + (xb * xn + yb * yn))
= xa * xn + yb * xn + (ya * yn + xb * yn) + (xb * xn + xb * ym + (yb * yn + yb * xm))
: by simp
... = (xa + yb) * xn + (ya + xb) * yn + (xb * (xn + ym) + yb * (yn + xm)) : by simp
... = (ya + xb) * xn + (xa + yb) * yn + (xb * (yn + xm) + yb * (xn + ym)) : by simp
... = ya * xn + xb * xn + (xa * yn + yb * yn) + (xb * yn + xb * xm + (yb*xn + yb*ym))
: by simp
... = xa * yn + ya * xn + (xb * xm + yb * ym) + (yb * xn + xb * yn + (xb * xn + yb * yn))
: by simp,
nat.add.cancel_right H3
theorem pmul_congr {p p' q q' : × } (H1 : p ≡ p') (H2 : q ≡ q') : pmul p q ≡ pmul p' q' :=
equiv_mul_prep H1 H2
theorem pmul_comm (p q : × ) : pmul p q = pmul q p :=
calc
(pr1 p * pr1 q + pr2 p * pr2 q, pr1 p * pr2 q + pr2 p * pr1 q) =
(pr1 q * pr1 p + pr2 p * pr2 q, pr1 p * pr2 q + pr2 p * pr1 q) : mul.comm
... = (pr1 q * pr1 p + pr2 q * pr2 p, pr1 p * pr2 q + pr2 p * pr1 q) : mul.comm
... = (pr1 q * pr1 p + pr2 q * pr2 p, pr2 q * pr1 p + pr2 p * pr1 q) : mul.comm
... = (pr1 q * pr1 p + pr2 q * pr2 p, pr2 q * pr1 p + pr1 q * pr2 p) : mul.comm
... = (pr1 q * pr1 p + pr2 q * pr2 p, pr1 q * pr2 p + pr2 q * pr1 p) : nat.add.comm
theorem mul.comm (a b : ) : a * b = b * a :=
eq_of_repr_equiv_repr
((calc
repr (a * b) = pmul (repr a) (repr b) : repr_mul
... = pmul (repr b) (repr a) : pmul_comm
... = repr (b * a) : repr_mul) ▸ !equiv.refl)
theorem pmul_assoc (p q r: × ) : pmul (pmul p q) r = pmul p (pmul q r) :=
by simp
theorem mul.assoc (a b c : ) : (a * b) * c = a * (b * c) :=
eq_of_repr_equiv_repr
((calc
repr (a * b * c) = pmul (repr (a * b)) (repr c) : repr_mul
... = pmul (pmul (repr a) (repr b)) (repr c) : repr_mul
... = pmul (repr a) (pmul (repr b) (repr c)) : pmul_assoc
... = pmul (repr a) (repr (b * c)) : repr_mul
... = repr (a * (b * c)) : repr_mul) ▸ !equiv.refl)
theorem mul.right_id (a : ) : a * 1 = a :=
eq_of_repr_equiv_repr (equiv_of_eq
((calc
repr (a * 1) = pmul (repr a) (repr 1) : repr_mul
... = (pr1 (repr a), pr2 (repr a)) : by simp
... = repr a : prod.eta)))
theorem mul.left_id (a : ) : 1 * a = a :=
mul.comm a 1 ▸ mul.right_id a
theorem mul.right_distrib (a b c : ) : (a + b) * c = a * c + b * c :=
eq_of_repr_equiv_repr
(calc
repr ((a + b) * c) = pmul (repr (a + b)) (repr c) : repr_mul
... ≡ pmul (padd (repr a) (repr b)) (repr c) : pmul_congr !repr_add equiv.refl
... = padd (pmul (repr a) (repr c)) (pmul (repr b) (repr c)) : by simp
... = padd (repr (a * c)) (pmul (repr b) (repr c)) : {(repr_mul a c)⁻¹}
... = padd (repr (a * c)) (repr (b * c)) : repr_mul
... ≡ repr (a * c + b * c) : equiv.symm !repr_add)
theorem mul.left_distrib (a b c : ) : a * (b + c) = a * b + a * c :=
calc
a * (b + c) = (b + c) * a : mul.comm a (b + c)
... = b * a + c * a : mul.right_distrib b c a
... = a * b + c * a : {mul.comm b a}
... = a * b + a * c : {mul.comm c a}
theorem zero_ne_one : (typeof 0 : int) ≠ 1 :=
assume H : 0 = 1,
show false, from succ_ne_zero 0 ((of_nat_inj H)⁻¹)
theorem eq_zero_or_eq_zero_of_mul_eq_zero {a b : } (H : a * b = 0) : a = 0 b = 0 :=
have H2 : (nat_abs a) * (nat_abs b) = nat.zero, from
calc
(nat_abs a) * (nat_abs b) = (nat_abs (a * b)) : (mul_nat_abs a b)⁻¹
... = (nat_abs 0) : {H}
... = nat.zero : nat_abs_of_nat nat.zero,
have H3 : (nat_abs a) = nat.zero (nat_abs b) = nat.zero, from mul.eq_zero H2,
or_of_or_of_imp_of_imp H3
(assume H : (nat_abs a) = nat.zero, nat_abs_eq_zero H)
(assume H : (nat_abs b) = nat.zero, nat_abs_eq_zero H)
definition integral_domain : algebra.integral_domain int :=
algebra.integral_domain.mk add add.assoc zero add.left_id add.right_id neg add.left_inv
add.comm mul mul.assoc (of_num 1) mul.left_id mul.right_id mul.left_distrib mul.right_distrib
zero_ne_one mul.comm @eq_zero_or_eq_zero_of_mul_eq_zero
/-
Instantiate ring theorems to int
-/
-- TODO: make this "section" when scoping bug is fixed
context port_algebra
open algebra
instance integral_domain
theorem mul.left_comm : ∀a b c : , a * (b * c) = b * (a * c) := algebra.mul.left_comm
theorem mul.right_comm : ∀a b c : , (a * b) * c = (a * c) * b := algebra.mul.right_comm
theorem add.left_comm : ∀a b c : , a + (b + c) = b + (a + c) := algebra.add.left_comm
theorem add.right_comm : ∀a b c : , (a + b) + c = (a + c) + b := algebra.add.right_comm
theorem add.left_cancel : ∀{a b c : }, a + b = a + c → b = c := @algebra.add.left_cancel _ _
theorem add.right_cancel : ∀{a b c : }, a + b = c + b → a = c := @algebra.add.right_cancel _ _
theorem neg_add_cancel_left : ∀a b : , -a + (a + b) = b := algebra.neg_add_cancel_left
theorem neg_add_cancel_right : ∀a b : , a + -b + b = a := algebra.neg_add_cancel_right
theorem neg_eq_of_add_eq_zero : ∀{a b : }, a + b = 0 → -a = b :=
@algebra.neg_eq_of_add_eq_zero _ _
theorem neg_zero : -0 = 0 := algebra.neg_zero
theorem neg_neg : ∀a : , -(-a) = a := algebra.neg_neg
theorem neg.inj : ∀{a b : }, -a = -b → a = b := @algebra.neg.inj _ _
theorem neg_eq_neg_iff_eq : ∀a b : , -a = -b ↔ a = b := algebra.neg_eq_neg_iff_eq
theorem neg_eq_zero_iff_eq_zero : ∀a : , -a = 0 ↔ a = 0 := algebra.neg_eq_zero_iff_eq_zero
theorem eq_neg_of_eq_neg : ∀{a b : }, a = -b → b = -a := @algebra.eq_neg_of_eq_neg _ _
theorem eq_neg_iff_eq_neg : ∀{a b : }, a = -b ↔ b = -a := @algebra.eq_neg_iff_eq_neg _ _
theorem add.right_inv : ∀a : , a + -a = 0 := algebra.add.right_inv
theorem add_neg_cancel_left : ∀a b : , a + (-a + b) = b := algebra.add_neg_cancel_left
theorem add_neg_cancel_right : ∀a b : , a + b + -b = a := algebra.add_neg_cancel_right
theorem neg_add_eq : ∀a b : , -(a + b) = -b + -a := algebra.neg_add_eq
theorem eq_add_neg_of_add_eq : ∀{a b c : }, a + b = c → a = c + -b :=
@algebra.eq_add_neg_of_add_eq _ _
theorem eq_neg_add_of_add_eq : ∀{a b c : }, a + b = c → b = -a + c :=
@algebra.eq_neg_add_of_add_eq _ _
theorem neg_add_eq_of_eq_add : ∀{a b c : }, a = b + c → -b + a = c :=
@algebra.neg_add_eq_of_eq_add _ _
theorem add_neg_eq_of_eq_add : ∀{a b c : }, a = b + c → a + -c = b :=
@algebra.add_neg_eq_of_eq_add _ _
theorem eq_add_of_add_neg_eq : ∀{a b c : }, a + -b = c → a = c + b :=
@algebra.eq_add_of_add_neg_eq _ _
theorem eq_add_of_neg_add_eq : ∀{a b c : }, -a + b = c → b = a + c :=
@algebra.eq_add_of_neg_add_eq _ _
theorem add_eq_of_eq_neg_add : ∀{a b c : }, a = -b + c → b + a = c :=
@algebra.add_eq_of_eq_neg_add _ _
theorem add_eq_of_eq_add_neg : ∀{a b c : }, a = b + -c → a + c = b :=
@algebra.add_eq_of_eq_add_neg _ _
theorem add_eq_iff_eq_neg_add : ∀a b c : , a + b = c ↔ b = -a + c :=
@algebra.add_eq_iff_eq_neg_add _ _
theorem add_eq_iff_eq_add_neg : ∀a b c : , a + b = c ↔ a = c + -b :=
@algebra.add_eq_iff_eq_add_neg _ _
definition sub (a b : ) : := algebra.sub a b
infix - := int.sub
theorem sub_self : ∀a : , a - a = 0 := algebra.sub_self
theorem sub_add_cancel : ∀a b : , a - b + b = a := algebra.sub_add_cancel
theorem add_sub_cancel : ∀a b : , a + b - b = a := algebra.add_sub_cancel
theorem eq_of_sub_eq_zero : ∀{a b : }, a - b = 0 → a = b := @algebra.eq_of_sub_eq_zero _ _
theorem eq_iff_sub_eq_zero : ∀a b : , a = b ↔ a - b = 0 := algebra.eq_iff_sub_eq_zero
theorem zero_sub_eq : ∀a : , 0 - a = -a := algebra.zero_sub_eq
theorem sub_zero_eq : ∀a : , a - 0 = a := algebra.sub_zero_eq
theorem sub_neg_eq_add : ∀a b : , a - (-b) = a + b := algebra.sub_neg_eq_add
theorem neg_sub_eq : ∀a b : , -(a - b) = b - a := algebra.neg_sub_eq
theorem add_sub_eq : ∀a b c : , a + (b - c) = a + b - c := algebra.add_sub_eq
theorem sub_add_eq_sub_sub_swap : ∀a b c : , a - (b + c) = a - c - b :=
algebra.sub_add_eq_sub_sub_swap
theorem sub_eq_iff_eq_add : ∀a b c : , a - b = c ↔ a = c + b := algebra.sub_eq_iff_eq_add
theorem eq_sub_iff_add_eq : ∀a b c : , a = b - c ↔ a + c = b := algebra.eq_sub_iff_add_eq
theorem eq_iff_eq_of_sub_eq_sub : ∀{a b c d : }, a - b = c - d → a = b ↔ c = d :=
@algebra.eq_iff_eq_of_sub_eq_sub _ _
theorem sub_add_eq_sub_sub : ∀a b c : , a - (b + c) = a - b - c := algebra.sub_add_eq_sub_sub
theorem neg_add_eq_sub : ∀a b : , -a + b = b - a := algebra.neg_add_eq_sub
theorem neg_add_distrib : ∀a b : , -(a + b) = -a + -b := algebra.neg_add_distrib
theorem sub_add_eq_add_sub : ∀a b c : , a - b + c = a + c - b := algebra.sub_add_eq_add_sub
theorem sub_sub_eq : ∀a b c : , a - b - c = a - (b + c) := algebra.sub_sub_eq
theorem add_sub_add_left_eq_sub : ∀a b c : , (c + a) - (c + b) = a - b :=
algebra.add_sub_add_left_eq_sub
theorem ne_zero_of_mul_ne_zero_right : ∀{a b : }, a * b ≠ 0 → a ≠ 0 :=
@algebra.ne_zero_of_mul_ne_zero_right _ _
theorem ne_zero_of_mul_ne_zero_left : ∀{a b : }, a * b ≠ 0 → b ≠ 0 :=
@algebra.ne_zero_of_mul_ne_zero_left _ _
definition dvd (a b : ) : Prop := algebra.dvd a b
infix `|` := dvd
theorem dvd.intro : ∀{a b c : } (H : a * b = c), a | c := @algebra.dvd.intro _ _
theorem dvd.ex : ∀{a b : } (H : a | b), ∃c, a * c = b := @algebra.dvd.ex _ _
theorem dvd.elim : ∀{P : Prop} {a b : } (H₁ : a | b) (H₂ : ∀c, a * c = b → P), P :=
@algebra.dvd.elim _ _
theorem dvd.refl : ∀a : , a | a := algebra.dvd.refl
theorem dvd.trans : ∀{a b c : } (H₁ : a | b) (H₂ : b | c), a | c := @algebra.dvd.trans _ _
theorem eq_zero_of_zero_dvd : ∀(a : ) {H : 0 | a}, a = 0 := @algebra.eq_zero_of_zero_dvd _ _
theorem dvd_zero : ∀a : , a | 0 := algebra.dvd_zero
theorem one_dvd : ∀a : , 1 | a := algebra.one_dvd
theorem dvd_mul_right : ∀a b : , a | a * b := algebra.dvd_mul_right
theorem dvd_mul_left : ∀a b : , a | b * a := algebra.dvd_mul_left
theorem dvd_mul_of_dvd_left : ∀{a b : } (H : a | b) (c : ), a | b * c :=
@algebra.dvd_mul_of_dvd_left _ _
theorem dvd_mul_of_dvd_right : ∀{a b : } (H : a | b) (c : ), a | c * b :=
@algebra.dvd_mul_of_dvd_right _ _
theorem mul_dvd_mul : ∀{a b c d : }, a | b → c | d → a * c | b * d :=
@algebra.mul_dvd_mul _ _
theorem dvd_of_mul_right_dvd : ∀{a b c : }, a * b | c → a | c :=
@algebra.dvd_of_mul_right_dvd _ _
theorem dvd_of_mul_left_dvd : ∀{a b c : }, a * b | c → b | c :=
@algebra.dvd_of_mul_left_dvd _ _
theorem dvd_add : ∀{a b c : }, a | b → a | c → a | b + c := @algebra.dvd_add _ _
theorem zero_mul_eq : ∀a : , 0 * a = 0 := algebra.zero_mul_eq
theorem mul_zero_eq : ∀a : , a * 0 = 0 := algebra.mul_zero_eq
theorem neg_mul_eq_neg_mul : ∀a b : , -(a * b) = -a * b := algebra.neg_mul_eq_neg_mul
theorem neg_mul_eq_mul_neg : ∀a b : , -(a * b) = a * -b := algebra.neg_mul_eq_mul_neg
theorem neg_mul_neg_eq : ∀a b : , -a * -b = a * b := algebra.neg_mul_neg_eq
theorem neg_mul_comm : ∀a b : , -a * b = a * -b := algebra.neg_mul_comm
theorem mul_sub_left_distrib : ∀a b c : , a * (b - c) = a * b - a * c :=
algebra.mul_sub_left_distrib
theorem mul_sub_right_distrib : ∀a b c : , (a - b) * c = a * c - b * c :=
algebra.mul_sub_right_distrib
theorem mul_add_eq_mul_add_iff_sub_mul_add_eq :
∀a b c d e : , a * e + c = b * e + d ↔ (a - b) * e + c = d :=
algebra.mul_add_eq_mul_add_iff_sub_mul_add_eq
theorem mul_self_sub_mul_self_eq : ∀a b : , a * a - b * b = (a + b) * (a - b) :=
algebra.mul_self_sub_mul_self_eq
theorem mul_self_sub_one_eq : ∀a : , a * a - 1 = (a + 1) * (a - 1) :=
algebra.mul_self_sub_one_eq
theorem dvd_neg_iff_dvd : ∀a b : , a | -b ↔ a | b := algebra.dvd_neg_iff_dvd
theorem neg_dvd_iff_dvd : ∀a b : , -a | b ↔ a | b := algebra.neg_dvd_iff_dvd
theorem dvd_sub : ∀a b c : , a | b → a | c → a | (b - c) := algebra.dvd_sub
theorem mul_ne_zero : ∀{a b : }, a ≠ 0 → b ≠ 0 → a * b ≠ 0 := @algebra.mul_ne_zero _ _
theorem mul.cancel_right : ∀{a b c : }, a ≠ 0 → b * a = c * a → b = c :=
@algebra.mul.cancel_right _ _
theorem mul.cancel_left : ∀{a b c : }, a ≠ 0 → a * b = a * c → b = c :=
@algebra.mul.cancel_left _ _
theorem mul_self_eq_mul_self_iff : ∀a b : , a * a = b * b ↔ a = b a = -b :=
algebra.mul_self_eq_mul_self_iff
theorem mul_self_eq_one_iff : ∀a : , a * a = 1 ↔ a = 1 a = -1 :=
algebra.mul_self_eq_one_iff
theorem dvd_of_mul_dvd_mul_left : ∀{a b c : }, a ≠ 0 → a * b | a * c → b | c :=
@algebra.dvd_of_mul_dvd_mul_left _ _
theorem dvd_of_mul_dvd_mul_right : ∀{a b c : }, a ≠ 0 → b * a | c * a → b | c :=
@algebra.dvd_of_mul_dvd_mul_right _ _
end port_algebra
-- TODO: declare appropriate rewrite rules
-- add_rewrite add_left_id add_right_id
-- add_rewrite add_comm add.assoc add_left_comm
-- add_rewrite sub_def add_inverse_right add_inverse_left
-- add_rewrite neg_add_distr
---- add_rewrite sub_sub_assoc sub_add_assoc add_sub_assoc
---- add_rewrite add_neg_right add_neg_left
---- add_rewrite sub_self
end int
/- tests -/
/- open int
eval -100
eval -(-100)
eval #int (5 + 7)
eval -5 + 7
eval 5 + -7
eval -5 + -7
eval #int 155 + 277
eval -155 + 277
eval 155 + -277
eval -155 + -277
eval #int 155 - 277
eval #int 277 - 155
eval #int 2 * 3
eval -2 * 3
eval 2 * -3
eval -2 * -3
eval 22 * 33
eval -22 * 33
eval 22 * -33
eval -22 * -33
eval #int 22 ≤ 33
eval #int 33 ≤ 22
example : #int 22 ≤ 33 := true.intro
example : #int -5 < 7 := true.intro
-/